Product Quality Evaluation in Physical Stores versus Online Stores - Mihaela ȘTIR (Expert Journal of Marketing, 2018)
In Romania, the value of online shopping reached 2.8 billion in 2017, 40% more than in 2016, being one of the highest increases in the European Union. However, the e-commerce market value is still small compared to other European countries, one of the main reasons that people prefer not to buy online is mistrust in the quality of the products offered. In order to gain insights into the criteria used by Romanian consumers to evaluate product quality, we conducted eight in depth interviews. The results show that there are a lot of similarities between attributes used to evaluate product quality in a physical store and attributes used to evaluate product quality in an online store. Meanwhile, the differences consists in the presence of customer reviews as the most relevant attribute for the online stores and price as the most relevant attribute for physical stores.